2014
DOI: 10.1038/labinvest.2014.108
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 expression for progression of oral squamous cell carcinoma and for self-clearance of apoptotic cells

Abstract: Milk fat globule-epidermal growth factor (EGF)-factor VIII (MFG-E8) is a secreted glycoprotein that promotes clearance of apoptotic cells by bridging phosphatidylserine on apoptotic cells and integrin avb3/5 on phagocytes. High expression of MFG-E8 has been reported in various types of cancer in humans. Apoptotic figures are frequently found in the surgical samples of oral squamous cell carcinoma (SCC) and carcinoma in situ, and we have often observed apoptotic carcinoma cells engulfed by macrophages or even b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…We examined MFG‐E8 expression in human esophageal squamous cell carcinoma using IHC staining and found that some of the cells abundantly express MFG‐E8, as shown in other types of cancer . As the IHC staining of the samples showed that the expression of MFG‐E8 was more abundant in cancer cells than in macrophages or other stromal cells, MFG‐E8 from cancer cells appears to play an important role in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We examined MFG‐E8 expression in human esophageal squamous cell carcinoma using IHC staining and found that some of the cells abundantly express MFG‐E8, as shown in other types of cancer . As the IHC staining of the samples showed that the expression of MFG‐E8 was more abundant in cancer cells than in macrophages or other stromal cells, MFG‐E8 from cancer cells appears to play an important role in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 87%
“…We examined MFG-E8 expression in human esophageal squamous cell carcinoma using IHC staining and found that some of the cells abundantly express MFG-E8, as shown in other types of cancer. [15][16][17][18][19][20]28,30,31 As the IHC staining of the samples showed that the expression of MFG-E8 was more abundant in cancer cells than in macrophages or other stromal cells, MFG-E8 from cancer cells appears to play an important role in the tumor microenvironment. Analysis of all patients examined showed that tumors with high MFG-E8 expression had a significantly higher possibility of having advanced lymph node and non-regional lymph node metastasis (M1), as previously suggested in malignant melanoma patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the wound-site, successful efferocytosis by mϕ achieves cleansing and resolution of inflammation (10-13). Milk fat globule-epidermal growth factor (EGF)-factor VIII (MFG-E8) is a secreted glycoprotein protein that promotes efferocytosis by bridging apoptotic cells on phagocytes with mϕ (14-15). MFG-E8 contains two EGF domains, a proline/threonine-rich domain, and two factor-VIII-homologous domains (15).…”
Section: Introductionmentioning
confidence: 99%
“…showed that tissue and serum exosomes from patients with prostate cancer had a higher expression level of MFGE8 than controls and that MFGE8‐induced efferocytosis lead to macrophage polarization towards a tumor‐promoting M2 phenotype. In addition, the immunohistochemical expression of MFGE8 in surgical specimens of human oral squamous cell carcinoma has been associated with some tumor clinicopathological features including size, stage and invasion patterns . An intensified MerTK signaling in the tumor tissues has been associated with cancer progression, metastasis and resistance to treatment …”
Section: Introductionmentioning
confidence: 99%